Validation of plantar pressure and reaction force measured by Moticon pressure sensor insoles on a Concept2 Rowing Ergometer - Barratt, G. K.; Bellenger, C.; Robertson, E. Y.; Lane, J.; Crowther, R. G. (Sensors, 2021)
The purpose of this study was to determine the reliability and validity of plantar pressure and reaction force measured using the Moticon and Pedar-x sensor insoles while rowing on a Concept2 ergometer. Nineteen participants performed four 500 m trials of ergometer rowing at 22-24 strokes/min; two trials wearing Moticon insoles and two wearing Pedar-x insoles in a randomised order. Moticon and Pedar-x insoles both showed moderate to strong test-retest reliability (ICC = 0.57-0.92) for mean and peak plantar pressure and reaction force. Paired t-test demonstrated a significant difference (p < 0.001) between Moticon and Pedar-x insoles, effect size showed a large bias (ES > 1.13), and Pearson`s correlation (r < 0.37) showed poor agreement for all plantar pressure and reaction force variables. Compared to Pedar-x, the Moticon insoles demonstrated poor validity, however, the Moticon insoles had strong reliability. Due to poor validity, caution should be used when considering Moticon insoles to assess changes in pressure and force reliably over time, across multiple trials or sessions. Moticon`s wireless and user-friendly application would be beneficial for assessing and monitoring biomechanical parameters in rowing if validity between measures of interest and Moticon`s results can be established.